PENERAPAN KONSELING KELOMPOK UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA KELAS VII A DI SMPN 1 MENGWI TAHUN PELAJARAN 2024/2025 - I Made Mahardhika; Ni Wayan Suastini; Ni Made Dwi Udiani; Yeni Fatma (Journal Prakarsa Paedagogia, 2024)
This study aims to evaluate and analyze the improvement in students' learning independence through group counseling for Class VII A students. The research subjects consisted of 7 students with low learning independence, selected from a total of 36 students in Class VII A. The research was conducted using a guidance and counseling action research (PTBK) approach in two cycles. The results after the first cycle showed an increase in learning independence ranging from 38.46% to 52.63%. When converted into an ideal minimum score, this translated to scores between 54% and 59%, which fell into the moderate category. The researchers noted that further improvement was necessary for optimal development. In the second cycle, the students' learning independence improved significantly, ranging from 33.93% to 43.64%, with ideal scores between 75% and 80%, which placed them in the high to very high category. Overall, there was an average increase of 38.15% in learning independence.